Prevalence of fetal ultrasonographic soft markers in antenatal women and their pregnancy outcomes: a cross-sectional study - Agarwal, Shaily; Sahu, Monica; Gupta, Renu; Lal, Pavika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Objectives: Estimating soft marker prevalence during first and second trimester ultrasound scans and determining the relationship between nuchal translucency (NT) measurements and sociodemographic variables in the antenatal population receiving care at our facility. Methods: This hospital-based observational study, conducted from January 2020 to November 2021, included 300 pregnant women receiving antenatal care at our institute. Soft markers studied included NT and absence of nasal bone for the first trimester and echogenic intracardiac focus (EICF), hyperechogenic bowel, choroid plexus cyst (CPC), mild renal pyelectasis, and limb shortening for the second trimester. For ultrasonographic examination, a HITACHI –ALOKA -6 USG equipment was used via transabdominal route. Wherever applicable, independent sample t test, chi-square test, and fisher's exact test were used to examine demographic factors and NT. To analyse the data, S.P.S.S version 23 was utilized. Results: The mean age of the participants was 24.96 years, and 41% (n=123) were primigravida and 59% (n=177) were multigravida. Most pregnant women (79%, n=237) were low-risk. Prevalence of Increased NT was 2.66% (n=9), hypoplasia or absence of NB was none, EICF was 2.33% (n=7), Hyperechogenic bowel was 0.33% (n=1), CPC was none, mild renal pyelectasis was 0.66% (n=2), and limb shortening was 0.33%. Relationship between obstetric risk factors and increased NT (2=12.22, p=0.006) and mean age of participants with increased NT (t=-2.625, p=0.009) was statistically significant. Conclusions: First-trimester fetal NT screening should be done for pregnant women over 30 and multigravida. Soft markers in pregnant women need a thorough diagnostic evaluation to rule out fetal abnormalities.